Islamic finance and social sustainability : parameters for developing a model for social impact measurement / Saadiah Mohamad and Nur Amirah Borhan - Saadiah, Mohamad; Nur Amirah, Borhan (Universiti Teknologi MARA, Perak, 2017)
To be true to the spirit of Islamic finance, embodied in the principles of maqasid al-shariah, developments in Islamic finance should contribute towards promoting social inclusion and reducing poverty. However, Islamic finance is criticised for the minimal social impact that it has created and its contribution towards promoting social sustainability. Thus, this paper aims to develop a comparative analysis of literature on the meaning, conceptualization and measurement models of social impact. Then, the paper uses maqasid al-shariah as a theoretical framework to conceptualise social impact and to propose a set of parametersthat can be used to measure the social impact of IFIs